Study of Dosage-Dependent Effects of Cytostatic Drugs Using a Fibroblast Cell Culture of the Human Nasal Mucosa - Yartsev, Vasily; Gabashvili, Anna; Atkova, Eugenia; Melnikov, Pavel; Nesterova, Tatiana (International Archives of Otorhinolaryngology, 2020)
Introduction Knowing a concentration at which cytostatic drugs are toxic for the nasal fibroblasts will enable the use cytostatic drugs in the clinical practice to prevent excessive cicatrization.Objective To determine the cytostatic concentrations of mitomycin С, doxorubicin, and 5-fluorouracil affecting nasal mucosa fibroblasts.Methods We obtained material during an endonasal dacryocystorhinostomy with the patient's informed consent. The cells were cultivated. Second- to fourth-passage cells were used in the experiments. The cells were stained for vimentin and cluster of differentiation 90 (CD90). An MTS test 3 (3-(4,5-dimethylthiazole-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium); cell viability test was performed.Results The cytostatic drugs have a toxic effect on cultivated fibroblasts of the nasal mucosa. This effect is dose-dependent. In terms of reducing the level of tissue fibrotisation in the nasal cavity, the most justified approach is to carry out an experimental study of the effect of mitomycin C, doxorubicin, and 5-fluorouracil at the concentrations of 0.25 mg/ml, 0.25 mg/ml, and 12.5 mg/ml respectively.Conclusion The authors argue that it is inappropriate to use these cytostatic drugs to conduct studies with the goal of analyzing their antifibrotic effect on the nasal mucosa at concentrations that are either lower or higher than the aforementioned ones.
Keywords: fibroblasts; fibrosis; mitomycin C; doxorubicin; 5-fluorouracil; cytostatic drugs